2018
DOI: 10.1016/j.chemosphere.2018.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Chlorella vulgaris mixotrophic growth enhanced biomass productivity and reduced toxicity from agro-industrial by-products

Abstract: Algal wastewater remediation has become attractive for a couple of years now, however the effectiveness of genetic toxicity reducing of some by-products through microalgae are still not well reported. This study aimed to evaluate the growth, nutrients and toxicity removal of Chlorella vulgaris cultivated under autotrophic and mixotrophic conditions in three agro-industrial by-products. Mixotrophic culture using corn steep liquor showed higher cell concentration, specific growth rate, maximum cell productivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 34 publications
3
33
1
1
Order By: Relevance
“…Along with photoautotrophy, several microalgal species are capable of performing chemoheterotrophic or mixotrophic metabolism, which is of interest for the treatment of industrial wastewater containing a high organic load. Among the most studied conventional microalgal strains is Chlorella vulgaris, which has been examined recently for its biomass production from food waste compost [23], sludge extracts [24], corn steep liquor, cheese whey and vinasse [25], textile waste effluent [26], tofu wastewater [27], and industrial dairy effluent [28]. Zhai et al [19] have demonstrated the high N (81.51%) and P (80.52%) removal efficiency of the widely used cyanobacterium Arthrospira platensis using a synthetic wastewater.…”
Section: Conventional Microalgae Used For Ww Tmentioning
confidence: 99%
“…Along with photoautotrophy, several microalgal species are capable of performing chemoheterotrophic or mixotrophic metabolism, which is of interest for the treatment of industrial wastewater containing a high organic load. Among the most studied conventional microalgal strains is Chlorella vulgaris, which has been examined recently for its biomass production from food waste compost [23], sludge extracts [24], corn steep liquor, cheese whey and vinasse [25], textile waste effluent [26], tofu wastewater [27], and industrial dairy effluent [28]. Zhai et al [19] have demonstrated the high N (81.51%) and P (80.52%) removal efficiency of the widely used cyanobacterium Arthrospira platensis using a synthetic wastewater.…”
Section: Conventional Microalgae Used For Ww Tmentioning
confidence: 99%
“…Melo et al [74] evaluated the growth, nutrients and toxicity removal of Chlorella vulgaris cultivated under autotrophic and mixotrophic conditions using corn steep liquor, cheese whey and vinasse as source of organic matter. The results demonstrated that corn steep liquor toxicity was totally eliminated and cheese whey and vinasse toxicity were minimized by C. vulgaris.…”
Section: Growth Microalgae Using Waste From Agro-industrymentioning
confidence: 99%
“…In this case, it is preferred for alga to grow under mixotrophic conditions and use hydrocarbon as the sole carbon source. Melo et al (2018) proved that when C. vulgaris was grown under mixotrophic conditions, the cellular productivity increased, and it becomes more effective to remove agro industrial by-products. The highest growth rate of C. vulgaris was obtained when grown under mixotrophic conditions than when grown under photoautotrophic conditions (Abreu et al, 2012).…”
Section: Estimation Of C Vulgaris Growthmentioning
confidence: 99%